Standardisasi Pengelolaan Dinas Perpustakaan dan Kearsipan Kabupaten Bondowoso - Fadil mubarok; Endah Triwisudaningsih; Arifia Retna Yunita (Jurnal Dirosah Islamiyah, 2024)
Library and archives management in Bondowoso Regency faces various challenges that affect the quality of services and administrative effectiveness. These challenges include a lack of clear guidelines, inadequate infrastructure, and the need to increase staff capacity. To overcome this problem, the Bondowoso Regency Library and Archives Service is implementing a standardization program which aims to improve the quality of library and archive services through the implementation of standard procedures and structured policies. This research aims to evaluate the implementation of standardization in library and archives management and analyze its impact on the quality of services and archives management in Bondowoso Regency. This research approach uses qualitative methods with data collection techniques in the form of in-depth interviews, participant observation and document study. Interviews were conducted with department heads, library and archives staff, and service users to explore their perceptions and experiences regarding standardization. Observations are carried out to observe the management practices implemented, while document studies include regulations, policies and annual reports to analyze existing policies and procedures. The collected data was analyzed thematically to identify patterns and relationships between relevant themes. The research results show that the implementation of standardization has had a significant positive impact on library and archive management in Bondowoso Regency. Standardization has helped in establishing clear operational guidelines, increasing staff capacity through training, and introducing information technology that supports efficient management of collections and archives. Service users reported an increase in the quality of information and satisfaction with library services, while archives staff reported an increase in understanding and better application of procedures in archive management. However, the research also identified several challenges, including limited resources, resistance to change, and the need for further support from relevant parties. In conclusion, standardization is an effective step in improving the quality of library and archive management. This research suggests that the Bondowoso District Library and Archives Service should continue to support the implementation of standards by providing adequate resources and building an organizational culture that supports change. In addition, the findings of this research can be a reference for other regions in designing and implementing better information and archive management policies.